INFLUENCE OF GREEN BRAND POSITIONING AND ATTITUDE ON GREEN PURCHASE INTENTION: GREEN BRAND KNOWLEDGE AS MODERATION - Manalu, Vigory Gloriman (ITB AAS Indonesia Surakarta, 2025)
This research aims to test the green purchasing intentions of consumers from West Java using variables such as green brand positioning and attitude towards green brands as an antecedent and green brand knowledge as a moderating variable. The exploration carried out in this research used the development theory of planned behavior (TPB). Green brand knowledge is included as a moderating variable to determine how much knowledge consumers have can increase their interest in green products. The population in this research came from the West Java region with special criteria who knew environmentally friendly products. Based on testing the direct relationship and moderating effect of the variables green brand positioning, attitude towards green brands, green brand knowledge and green purchase intention, it was found that the four proposed hypotheses were supported. This research provides an idea of the intention to purchase green products in West Java, where consumers are aware of protecting the environment. Awareness of protecting the environment gives consumers good knowledge of green brands, which can increase green purchasing intentions.